2006
DOI: 10.1074/jbc.m510680200
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Mechanomodulatory Role for p38 MAPK in Embryonic Joint Articular Surface Cell MEK-ERK Pathway Regulation

Abstract: Mechanisms regulating cell behavior and extracellular matrix composition in response to mechanical stimuli remain unresolved. Our previous studies have established that the MEK-ERK cascade plays a specific role in the mechano-dependent joint formation process by promoting the assembly of pericellular matrices reliant upon hyaluronan (HA) for their integrity. Here we demonstrate: (i) novel cross-talk between p38 MAPK and MEK-ERK signaling pathways that is specific for mechanical stimuli and (ii) a role for p38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 61 publications
6
25
0
Order By: Relevance
“…4), common for melanoma cells (1,37). This was efficiently prevented by blocking MAPK/ERK kinase 1/2 (U0126) and surprisingly by inhibition of p38, implying a possible cross-talk between p38 and ERK in response to, for example, mechanical stress as has recently been reported (23,38,39). As expected, phosphorylation of ERK1/2 was influenced neither by the JAK nor by the Src inhibitors.…”
Section: Increased Cell Density -Dependent Stat3 Activation In Melanosupporting
confidence: 52%
“…4), common for melanoma cells (1,37). This was efficiently prevented by blocking MAPK/ERK kinase 1/2 (U0126) and surprisingly by inhibition of p38, implying a possible cross-talk between p38 and ERK in response to, for example, mechanical stress as has recently been reported (23,38,39). As expected, phosphorylation of ERK1/2 was influenced neither by the JAK nor by the Src inhibitors.…”
Section: Increased Cell Density -Dependent Stat3 Activation In Melanosupporting
confidence: 52%
“…A recent study in AS cells has shown that inhibition of p38-activation by the antagonist SB203580 inhibits activation of ERK in response to a mechanical stimulus. 5 In contrast, inhibition of the MEK/ERK pathway had no effect upon the activation of p38. We have therefore also examined in this study the effects of inhibiting the p38 pathway upon the levels of ERK activation in response to a mechanical stimulus.…”
Section: Introductionmentioning
confidence: 92%
“…3 In both cardiac myocytes and cells derived from the joint articular surface (AS) there is now a considerable body of evidence that signalling pathways involving the mitogen-activated protein kinases (MAPKs) are crucial to mediating the responses to mechanical stimuli. 4,5 In particular it has been demonstrated that both p38 and extracellular regulated kinase (ERK) pathways can be co-activated in response to a mechanical stimulus and that physiological responses may involve cross-talk between these different pathways. 5 The role that these different MAPK pathways play both singly and in combination on the regulation of mechanically induced alterations in skeletal muscle phenotype is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation is that constitutive ERK1/2 activation in these cells is necessary but not sufficient for IGFBP-6-dependent migration as has been suggested previously for H-ras-induced migration (49). Constitutive ERK1/2 activation may result in downstream cross-talk with IGFBP-6-induced p38 MAPK activation thereby resulting in the migration response (52)(53)(54)(55). Alternatively, MAPK kinase may also activate kinases other than ERK1/2 and mediate alternative signaling pathways (56,57).…”
Section: Discussionmentioning
confidence: 99%